2022
DOI: 10.3390/agronomy12081908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Proportion Intercropping on Oat and Common Vetch Yields and Nutritional Composition at Different Growth Stages

Abstract: Crop yield mainly depends on environment and cultivation practices that vary according to a growing environment. However, an oat (Avena sativa L.)-common vetch (Vicia sativa L.) intercrop system has not been fully developed in the agro-pastoral ecotone of Inner Mongolia, China. This study evaluated the effects of seven treatments, including five oat-common vetch intercropping patterns, sole oat, and sole vetch on yield and quality performance at different growth periods [75 days after sowing (DAS), 90 DAS, 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Genetics and cultivation conditions, but not climate, are the main determinants of forage nutritional quality (Sohail et al, 2021). Legumes usually have higher CP contents and lower ADF and NDF contents than those of cereals (Qu et al, 2022). In our study, CP content, DMD, and RFV values of mixed crops were higher than monocultures, and no significant differences were observed between the two experimental sites.…”
Section: Discussionmentioning
confidence: 99%
“…Genetics and cultivation conditions, but not climate, are the main determinants of forage nutritional quality (Sohail et al, 2021). Legumes usually have higher CP contents and lower ADF and NDF contents than those of cereals (Qu et al, 2022). In our study, CP content, DMD, and RFV values of mixed crops were higher than monocultures, and no significant differences were observed between the two experimental sites.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the common vetch monocrop had the highest CP concentration at 14.88%. Another study found that CP yields were greatest with a 3:1 ratio of oats to common vetch, increasing 21.3 and 6.1% over oats alone and wild peas alone, respectively (Qu et al, 2022). However, in this semi-arid region under summersowing conditions, the highest CP yield (696 kg ha −1 ) was in the oat-common vetch intercrop with an 80:20 seeding ratio.…”
Section: Crude Proteinmentioning
confidence: 94%